MEMBANGUN SEMANGAT NASIONALISME DI SEKOLAH MELALUI KEARIFAN LOKAL - Endah Marwanti (Universitas Sarjanawiyata Tamansiswa, 2016)
The great experience we’ve gained from the history of the struggle of our nation. From history we can know and understand how big a difference, antagonism, and exchange of ideas is able to deliver us to the threshold of independence. With the great ideas of the leaders, Indonsia nation can understand the importance of unity. With united without thinking about differences, Indonesian people are able to overcome the various occupation. The spirit of unity is strengthened by threshold the nation’s independence. From identity, the identity of the Indonesian nation is getting stronger in the eyes of the world. Therefore, the spirit of nationalism younger generation at this time need to be cultivated again so as not to eroded the advance technology. Rapid technological progress could fade nationalism. To fortify this understanding of Pancasila, the 1945 Constitution, manners should be encouraged further, especially in education. Education should put forward the noble values of national culture. The noble values of the nation’s cultural or known by the local moral values is able to counteract the erosion of nationalism younger generation of the swift effect of globalization. The values of local wisdom wisdom in this is the embodiment of the ideals of a nation that is balanced, both physically and mentally. Local knowledge acts as a filter for the values come from outside, local knowledge can also be used to dampen the shocks that are internal. For instance conflicts that tribe or tribal community. Enterprises to disseminate the great value in a particular culture will be formally an appreciation and a sense of pride in those values. With the pride of the young generation will emerge a strong passion for applying them in public life.